Trust as a Mediator between Secure Attachment Style and Marital Adjustment in Married Individuals - Aqsa Yaqoob, Nasreen Bano (Pakistan Journal of Psychology, 2020)
The objective of the current study was to examine the mediating effect of trust between secure attachment style and marital adjustment in married individuals. The sample of 238 married individuals including 100 males and 138 females with age ranges from 20-60 years (M = 35.9, SD = 9.69) were recruited purposefully from different areas of Karachi-Pakistan. Measures used in the study along with demographic form were Trust in Close Relationship Scale (Rempel, Holmes, & Zanna, 1985), Adult Attachment Scale (Collins & Read, 1990) and Marital Adjustment Test (Locke &Wallace, 1959). Results of mediation analysis indicate that trust significantly mediated the association between secure attachment style and marital adjustment. Study findings highlight the importance of trust linking secure attachment style with marital adjustment in married individuals. Moreover, in clinical practice the marital therapists can use research findings related to trust and secured attachment to plan interventions to help the couples get over their marital problems.